2015
DOI: 10.1016/j.neuroimage.2014.11.058
|View full text |Cite
|
Sign up to set email alerts
|

Partial volume correction in quantitative amyloid imaging

Abstract: Amyloid imaging is a valuable tool for research and diagnosis in dementing disorders. As positron emission tomography (PET) scanners have limited spatial resolution, measured signals are distorted by partial volume effects. Various techniques have been proposed for correcting partial volume effects, but there is no consensus as to whether these techniques are necessary in amyloid imaging, and, if so, how they should be implemented. We evaluated a two-component partial volume correction technique and a regional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
240
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 212 publications
(248 citation statements)
references
References 43 publications
6
240
2
Order By: Relevance
“…In work by Drzezga et al on 11 C-Pittsburgh compound B, PVEC had no relevant impact on the apolipoprotein E4 effect in AD patients (19). More recently, Su et al applied PVEC to simulated and human 11 C-Pittsburgh compound B data and demonstrated that PVEC might improve the detection of subtle changes in Ab binding over time (20). Thomas et al used different PVEC approaches on 18 F-flutemetamol PET data; in accordance with our results and depending on the brain region investigated, the modified Müller-Gärtner method yielded different SUVR results in different cohorts (21).…”
Section: Discussionmentioning
confidence: 99%
“…In work by Drzezga et al on 11 C-Pittsburgh compound B, PVEC had no relevant impact on the apolipoprotein E4 effect in AD patients (19). More recently, Su et al applied PVEC to simulated and human 11 C-Pittsburgh compound B data and demonstrated that PVEC might improve the detection of subtle changes in Ab binding over time (20). Thomas et al used different PVEC approaches on 18 F-flutemetamol PET data; in accordance with our results and depending on the brain region investigated, the modified Müller-Gärtner method yielded different SUVR results in different cohorts (21).…”
Section: Discussionmentioning
confidence: 99%
“…Deposition of PiB in brain regions of interest was determined using FreeSurfer version 5.1 software (Martinos Center for Biomedical Imaging), 32,34,35 and a standardized uptake value ratio (SUVR) corrected for partial volume effects 36 was calculated for each region of interest. The mean cortical SUVR was calculated from FreeSurfer regions within the prefrontal cortex, precuneus, and temporal cortex.…”
Section: Methodsmentioning
confidence: 99%
“…The SUVR of the prefrontal cortex, temporal lobe, gyrus rectus and precuneus were averaged to calculate a total cortex SUVR. An SUVR of 1·3 was used to stratify the cohort based on amyloid positivity (PiB- < 1·3, PiB+ ≥ 1·3) [20]. …”
Section: Methodsmentioning
confidence: 99%